Anticonvulsant Study of Thiadiazoles and Pheno - Singh, Payal; Kumar, Pankaj; Singh, Jai; Kumar, Ashok (Asian Journal of Chemistry, 2010)
Ethyl-3-heteroarylacetates, 1-(3'-heteroarylacetyl)- semicarbazides/thiosemicarbazides, 2-amino-5-(3'-heteroarylmethylene)- 1,3,4-oxadiazoles/thiadiazoles, 5-(2'- heteroaryl methylene-1',3',4'-oxadiazol-2'-yl/thiadiazol-2'-yl)- 2-oxo/thiobarbituric acid, have been prepared. Their structures have been confirmed by TLC, elemental analysis, infrared spectra, NMR spectra and mass spectra. They have been screened for their anticonvulsant activity and ALD50.